2017
DOI: 10.1097/spv.0000000000000406
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Fellowship Training for Female Pelvic Medicine and Reconstructive Surgery

Abstract: There are several FPMRS fellowship models. A significant proportion of PDs would like a more integrated fellowship program, and an overwhelming majority note benefits for themselves and their fellows that result from increased contact with a diverse FPMRS faculty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…In addition, access to more comprehensive procedure data is limited and is proprietary to the ACGME. However, strengths of this study include a high response rate and consistent findings with another survey study 6 conducted 5 years ago indicating that these patterns have persisted.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In addition, access to more comprehensive procedure data is limited and is proprietary to the ACGME. However, strengths of this study include a high response rate and consistent findings with another survey study 6 conducted 5 years ago indicating that these patterns have persisted.…”
Section: Discussionsupporting
confidence: 71%
“…For those programs who would accept either urology-trained or gynecology-trained applicants but have received insufficient applications, there may need to be an increase in flexibility regarding training length and advertising strategies. In a study by Lake and Rickey, 6 60% of surveyed FPMRS fellowship programs would require a 3-year fellowship regardless of residency training and 93% would have the same rotation schedule. This is a similar finding to our study cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is most likely related to fellowship training and that the majority of female pelvic medicine and reconstructive surgery subspecialists are from a gynecology background, and the majority of urologists and "other" specialists in this cohort did not undergo extended training for performing these procedures. 23 The strongest predictors of GUTI in this study were intraoperative surgical factors, including lysis of adhesions, hematoma, and blood transfusion. These factors may reflect an increased difficulty of the surgical case, for example, the alteration of normal anatomy due to prior surgery or conditions such as endometriosis requiring complex dissection, and have also been associated with other intraoperative complications at the time of hysterectomy such as bowel injury.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, we found that surgical procedures performed by nongynecologic surgeons, urologists, and “other” specialties were significantly more likely to be associated with GUTI. This is most likely related to fellowship training and that the majority of female pelvic medicine and reconstructive surgery subspecialists are from a gynecology background, and the majority of urologists and “other” specialists in this cohort did not undergo extended training for performing these procedures 23 …”
Section: Discussionmentioning
confidence: 99%